Microwave Imaging with Modified Stack Type PIFA Antenna utilizing SAR Algorithm - Kiran, Kadiyam Sai; Asok, Athul O; Gokul Nath, S J; Dey, Sukomal (2022 IEEE Microwaves, Antennas, and Propagation Conference (MAPCON), 2022)
This paper describes a Planer Inverted F Antenna (PIFA) that can be used as a microwave imaging transducer. The planned antenna has a peak gain of 4.6 dBi at 1.7 GHz and operates between 1.68 and 1.71 GHz. The shape and performance of the proposed antenna are first investigated. This study investigates its applicability for imaging two cylindrical metallic objects followed by a metallic beam veiled by a cotton material.